2010
DOI: 10.1260/1757-482x.2.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Issues in CFD Simulation of Brown Coal Combustion in a Utility Furnace

Abstract: This paper describes the mathematical formulation and modelling issues of a computational fluid dynamics (CFD) model of a 375 MW utility furnace. This tangentially-fired furnace is fuelled by high moisture content brown coal from coal mines at Latrobe Valley in Victoria, Australia. The influences of different turbulence models, particle dispersion, and radiation models on the CFD prediction are investigated. Two turbulence models, standard k-ε model and Shear-Stress Transport (SST) model, provide similar predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Up till now, none of the solid fuel combustion submodels has been validatd for pressurized oxy-combustion environment. In the present work, the sub-models that have been extensively validated under atmospheric pressure oxy-coal combustion environment are used[4,[29][30][31][32][33][34]. It has been shown that RANS is able to provide reasonable agreement between experiments and CFD simulations under atmospheric pressure oxy-combustion condistions.…”
mentioning
confidence: 99%
“…Up till now, none of the solid fuel combustion submodels has been validatd for pressurized oxy-combustion environment. In the present work, the sub-models that have been extensively validated under atmospheric pressure oxy-coal combustion environment are used[4,[29][30][31][32][33][34]. It has been shown that RANS is able to provide reasonable agreement between experiments and CFD simulations under atmospheric pressure oxy-combustion condistions.…”
mentioning
confidence: 99%
“…Turbulence is modeled using the standard k –ε turbulence model. This was chosen after testing a number of turbulence models for coal combustion in a non-swirl burner, gas–particle flows through rectangular jets inclined to a cross-flow, and brown coal combustion in a furnace . The second case is representative of air and coal particle flows through the slot burners used in the tangentially fired furnace.…”
Section: Cfd Model Descriptionmentioning
confidence: 99%
“…In our previous work, , the CFD model used here was validated by comparing the FGET, concentration of flue gas components, total boiler heat supply, and wall incident heat fluxes to power plant measurements. Additionally, validation of submodels for gas–particle flows, coal and volatile combustion, and turbulence , was performed on simpler flows, where more detailed measurements could be taken under controlled operating conditions.…”
Section: Cfd Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) evaporation/drying model, (3) devolatilisation model, (4) char combustion model, (5) turbulence model, (6) turbulence-reaction interaction model (gas phase reaction models), (7) radiation model, (8) soot model, (9) NOx model, (10) SOx model, (11) slagging model. Figure 2, adapted from Tian et al (2010a) shows some sub-models available in the commercial CFD code ANSYS/CFX 14.…”
Section: Introductionmentioning
confidence: 99%